Current status of the citrus leprosis virus (cilv-c) and its vector brevipalpus phoenicis (geijskes) (2012)
The Citrus leprosis virus CiLV-C is a quarantine disease of economic importance. Over the past 15 years, this disease has spread to several countries of Central and South America. Colombia has about 45,000 hectares of citrus planted with an annual production of 750,000 tonnes. The CiLV-C has only been detected in the departments of Meta, Casanare and recently Tolima. Meta has 4,300 hectares representing 10% of the national cultivated area, and Casanare, where CiLV-C appeared in 2004, has no more than 500 ha planted with citrus. The presence of the citrus leprosis virus in Colombia could affect the international market for citrus, other crops and ornamental plants with the United States and other countries without the disease. The false spider mite Brevipalpus phoenicis (Geijskes) (Acari: Tenuipalpidae) is the main vector of the CiLV-C. Diseasen management is based on control programs of the vector and diminishing host plants. Chemical mite control is expensive, wasteful and generates resistance to different acaricides. This paper provides basic information on CiLV-C and its vector, advances in diagnosis and methods to control the disease and prevention of its spread. Source photographs: Figs. 1-4: León M., G.